Droga lepszego jutra (Gdańsk : [s.n.], 1955)
Plakat propagandowy zachęcający do wstępowania do spółdzielni rolniczych.
Keywords: Spółdzielnie -- Polska -- 1945-1970 -- plakaty; Rolnictwo -- Polska -- 1945-1970 -- plakaty; Propaganda -- Polska -- 1945-1970 -- plakaty